Kajian Daya Dukung Beras di Kabupaten Pekalongan - Dimas Suryo Aji; Sri Rahayu (Jurusan Perencanaan Wilayah dan Kota, 2020)
Pekalongan Regency is a rice-producing district and one of the rice barns in Central Java Province. However, the high conversion of agricultural land has caused a decrease of the agricultural land in Pekalongan Regency. One of them is the construction of Pemalang-Batang highway which spent 175,252 m2 of land converted into a highway. In addition, Rob flood that occurred on the coast of Pekalongan Regency has damaged the agricultural land and no longer productive. These phenomenon can impact the decrease of the paddy fields land area as well as the productivity which also has an impact on the reduction of food carrying capacity and weakening of food security. The aim of this research is to examine the carrying capacity of rice in Pekalongan Regency. The result of this research show that the carrying capacity of rice in Pekalongan Regency in 2018 and 2028 has value more than one, so Pekalongan Regency is able to provide rice needs for its residents independently. In 2018, there were thirteen districts that had a surplus while six sub-districts had a deficits . In 2028 there were three sub-districts which changed their carrying capacity into deficits, namely Talun, Paninggaran, and Subdistrict Subdistrict